Monitoring of the treatment effect of the secondary myopathy syndrome in patients with juvenile rheumatoid arthritis - Dudnyk, V. M.; Bereznyckyi, O. V.; Vyzhga, Yu. V. (Journal of Education, Health and Sport, 2015)
Dudnyk V. M., Bereznyckyi O. V., Vyzhga Yu. V. Monitoring of the treatment effect of the secondary myopathy syndrome in patients with juvenile rheumatoid arthritis. Journal of Education, Health and Sport. 2015;5(8):443-447. ISSN 2391-8306. DOI10.5281/zenodo.31323 http://dx.doi.org/10.5281/zenodo.31323 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A443-447 https://pbn.nauka.gov.pl/works/632554 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 24.09.2015. Monitoring of the treatment effect of the secondary myopathy syndrome in patients with juvenile rheumatoid arthritis V. M. Dudnyk, O. V. Bereznyckyi, Yu. V. Vyzhga Vinnitsya national medical university N.I. Pirogov memorial Abstaract The syndrome of the secondary myopathy is one of the pathologies that is deeply spreaded in doctor’s practice and has a tendency to be increased being 30 – 60% of all chronicle pain syndromes in rheumatology practice. We provided examination of 43 patients with JRA to monitor effect of the treatment. The data presents that development of the secondary myopathy syndrome in patients with JRA is characterized with severe clinical currency of the disease, high inflammatory activity and significant influence on the quality of patient’s life so needed to be treated specific. Key words: secondary myopathy, juvenile rheumatoid arthritis.